BLOOD MIMICKING FLUID FOR APPLICATION IN ANGIOGRAPHY IMAGING: THE EFFECT OF SURFACTANT ADDITION TOWARDS DENSITY AND VISCOSITY - Chai, Shan Jet; Shuib, Anis Suhaila; Phang, Siew Wei; Muda, Ahmad Sobri; Ahmad Sabri, Muhd Izzat (Asian Journal Of Medical Technology, 2023)
Modern 3D anatomical modelling and surgical simulation provide surgeons technical training to practice realistic pre-surgery rehearsals, adopt with patient-specific anatomical structures and prepare for operation procedures with minimal health risks on patients. Blood mimicking fluid is a biomimetic innovation developed for applications in 3D medical simulator, to mimic the non-Newtonian fluid properties of human blood. The ongoing challenge in blood mimicking fluid development is to replicate the shear-thinning behaviour and apparent viscosity of blood over a shear rate range of 0-1000 s-1 that occur in human blood vessels. There are limited investigation about the effect of surfactant concentration towards the density and viscosity of blood mimicking fluid. Surfactant is added in blood mimic to ensure the mixing of materials are homogenous. The purpose of this research is to investigate the effect of surfactant addition in blood mimicking fluids comprised of water-glycerol based fluid, xanthan gum , corn starch and contrast agent. The density and viscosity were analysed using a rheometer and densitometer, respectively. The increasing of surfactant concentration in blood mimicking fluid is discovered to have no major influence on the blood mimicking fluid density but increased the overall shear thinning viscosity of blood mimicking fluid.